Tattoo ink exposure is associated with lymphoma and skin cancers – a Danish study of twins - Signe Bedsted Clemmensen; Jonas Mengel-From; Jaakko Kaprio; Henrik Frederiksen; Jacob von Bornemann Hjelmborg (BMC Public Health)
Abstract Background We aim to study the potential association between tattoo ink exposure and development of certain types of cancers in the recently established Danish Twin Tattoo Cohort. Tattoo ink is known to transfer from skin to blood and accumulate in regional lymph nodes. We are concerned that tattoo ink induces inflammation at the deposit site, leading to chronic inflammation and increasing risk of abnormal cell proliferation, especially skin cancer and lymphoma. Methods We conducted two designs of twin studies to improve confounder control: A cohort study of 2,367 randomly selected twins and a case-control study of 316 twins born in the period 1960–1996. Cancer diagnoses (ICD-10) were retrieved from the Danish Cancer Registry and tattoo ink exposure from the Danish Twin Tattoo survey from 2021. The analysis addressed effects of time-varying exposure. Results In the case-control study, individual-level analysis resulted in a hazard of skin cancer (of any type except basal cell carcinoma) that was 1.62 times higher among tattooed individuals (95% CI: 1.08–2.41). Twin-matched analysis of 14 twin pairs discordant for tattoo ink exposure and skin cancer showed HR = 1.33 (95% CI: 0.46–3.84). For skin cancer and lymphoma, increased hazards were found for tattoos larger than the palm of a hand: HR = 2.37 (95% CI: 1.11–5.06) and HR = 2.73 (95% CI: 1.33–5.60), respectively. In the cohort study design, individual-level analysis resulted in a hazard ratio of 3.91 (95% CI: 1.42–10.8) for skin cancer and 2.83 (95% CI: 1.30–6.16) for basal cell carcinoma. Conclusion In conclusion, our study suggests an increased hazard of lymphoma and skin cancers among tattooed individuals, demonstrated through two designs: a twin cohort and a case-cotwin study. We are concerned that tattoo ink interacting with surrounding cells may have severe consequences. Studies that pinpoint the etiological pathway of tattoo ink induced carcinogenesis are recommended to benefit public health.